FREQUENCY AND PATTERN OF RETINOPATHY IN NEWLY DIAGNOSED TYPE 2 DIABETIC PATIENTS AT TERTIARY CARE SETTINGS IN ABBOTTABAD - Hayat, Atif Sitwat; Khan, Abdul Haque; Baloch, Ghulam Hussian; Shaikh, Naila (Journal of Ayub Medical College Abbottabad, 2012)
Background: Retinopathy is one of the most frequent and serious complication of diabetes mellitus and leading cause of blindness worldwide. The objective of this study was to determine frequency and pattern of retinopathy in newly diagnosed type 2 diabetic patients at tertiary care settings in Abbottabad. Methods: This was a descriptive cross-sectional comparative study being conducted at Ayub Teaching Hospital and Northern Institute of Medical Sciences Abbottabad. It included 100 newly diagnosed type 2 diabetic patients who were attending diabetic clinics of these tertiary care hospitals. Already diagnosed type 2 patients taking anti-diabetic medication, type 1 diabetes mellitus, hypertension, retinal vasculitis, retinal vessel occlusion, and sickle cell retinopathy were excluded. After pupillary dilatation, detailed fundoscopic examination was carried out via direct ophthalmoscopy and further confirmed by an ophthalmologist. According to fundoscopic findings, retinopathy was graded into background, pre-proliferative and proliferative types. Results: Total 100 patients were included, with mean age 45.1±3.2 years, 60% of them were females. Overall, 17% of type 2 diabetic patients had retinopathy within one month of diagnosis. Background retinopathy was predominant (12%) followed by pre-proliferative (4%) and proliferative (1%) lesions. Conclusion: Frequency of retinopathy in newly diagnosed type 2 diabetic patients seems to be higher than previous reports and background lesions were predominant. Detailed fundoscopic examination of all newly type 2 diabetic patients at the time of diagnosis is of paramount importance. Keywords: Frequency, type 2 diabetes mellitus, retinopathy, fundoscopic examination